2022
DOI: 10.1371/journal.pone.0267124
|View full text |Cite
|
Sign up to set email alerts
|

Thrombocytosis and abnormal liver enzymes: A trigger for investigation of underlying malignancy

Abstract: Background Thrombocytosis is often an incidental finding in primary care with a range of causes. Despite evidence of a strong association between thrombocytosis and malignancy, guidelines for investigating thrombocytosis in the absence of red flag symptoms remain unclear. A novel automated system of laboratory analysis, intelligent Liver Function Testing (iLFT), launched in Tayside in 2018 and has identified a patient group with thrombocytosis and abnormal liver test (LFT) results. This study analysed the outc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…On further investigation, it was found that the specific combination of elevated alkaline phosphatase (>130 U/L) and platelets (>400 × 10 9 /L) in individuals over 40 years of age had a positive predictive value (PPV) of 20% for malignancy. When this was tested in a validation cohort of 71,652 patients, the PPV was 30.6%, vastly exceeding the 3% investigation threshold recommended by the National Institute for Health & Care Excellence for malignancy risk and warranting further (routine) investigation [39,40].…”
Section: Identification Of Patients With Possible Malignancymentioning
confidence: 99%
“…On further investigation, it was found that the specific combination of elevated alkaline phosphatase (>130 U/L) and platelets (>400 × 10 9 /L) in individuals over 40 years of age had a positive predictive value (PPV) of 20% for malignancy. When this was tested in a validation cohort of 71,652 patients, the PPV was 30.6%, vastly exceeding the 3% investigation threshold recommended by the National Institute for Health & Care Excellence for malignancy risk and warranting further (routine) investigation [39,40].…”
Section: Identification Of Patients With Possible Malignancymentioning
confidence: 99%